Pattern of Maxilofacial Trauma inPatients Reporting at Liaquat UniversityHospital Hyderabad (Medical Forum Monthly, 2024)
Objective: The aim of present study was to evaluate the pattern of maxillofacial trauma in patients reporting at Liaquat University Hospital Hyderabad.Study Design: Observational / descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Oral and Maxillofacial Surgery Outpatient Department of Liaquat University Hospital from 01-01-2014 to 31-12-2015.Materials and Methods: This study was to analyze the age, gender and site of facial fracture of patients due to road traffic accidents, assault, falls, gunshot and sports injuries . Data relating to 136 patients was collected. The diagnosis of the maxillofacial trauma was done on the basis of history, clinical features and appropriate radiographs. All the relevant information was recorded on proforma.Results: Most prevalent age of trauma was 21-30 years teenagers, male 104 (76%) outnumbered the female 32 (24%) with ratio of 4:1. The most common fractured bone of midface was zygomatic bone n=52 (38.3%) and the most common region of mandibular fracture was parasymphysis n=34(25.0%).Conclusion: Trauma is a main cause of fracture of facial bones especially in the young male population of Pakistan. Zygomatic bone fracture and parasymphseal regions are most common fracture site.